The case of the missing maid eaudiobook - Osler, Rob (Harriet Morrow Investigates, 2025)
Rough-around-the-edges Harriet Morrow has long been drawn to the idea of whizzing around the city on her bicycle as a professional detective, solving crimes for a living without having to take a husband. She seizes the chance when the prestigious Prescott Agency hires her as its first woman operative. The move sparks controversy—with skeptical male colleagues, a high-strung office secretary, and her boss, Mr. Theodore Prescott, all waiting for her to unravel under the pressure . . . Harriet has an assignment: Discover the whereabouts of a missing maid from one of the most extravagant mansions on Prairie Avenue. Owner Pearl Bartlett has a reputation for sending operatives on wild goose chases around her grand estate, but Harriet believes the stunningly beautiful Agnes Wozniak has indeed vanished under mysterious circumstances . . . With Mr. Prescott pushing a hard deadline, Harriet's burgeoning career depends on working through a labyrinth of eccentric characters and murky motives in a race to discover who made Agnes disappear. When her search leads to Chicago's Polish community and a new friendship in Agnes's charming older sister, Barbara, clues scattered across the city slowly reveal just how much depends on Harriet's inexperienced investigation for answers . . . and the deep danger that awaits once she learns the truth.